Wizerunek przedsiębiorstwa - problemy definicyjne - Daszkiewicz, Magdalena (Corporate Image - Problems of Definition, 2008)
The article is an attempt to make an advance in the understanding of the concept of corporate image. The author made the marketing literature review which presents different viewpoints of corporate image definition. In attempt to understand the problems of corporate image definition the author identifies its relationship with corporate reputation and corporate identity. The article presents corporate image components and images which can impact perception of firms in different aspects of their activities. To clarify the essence of corporate image the author also we discusses models used to describe the process of corporate image creation.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 33, s. 27-41